Patterning Vertically Grown Gold Nanowire Electrodes for Intrinsically Stretchable Organic Transistors. (24th October 2018) - Zhu, Bowen; Gong, Shu; Lin, Fenge; Wang, Yan; Ling, Yunzhi; An, Tiance; Cheng, Wenlong
Abstract: Advances in large‐area organic electronics for sensor arrays and electronic skins demand highly stretchable, patternable, and conformal electrodes to minimize contact resistance when sensing devices are mechanically deformed. Gold is an excellent electrode material with work function matching well with p‐type organic transistors. However, it is non‐trivial to fabricate highly stretchable gold electrodes for stretchable organic electronics. Here, by combining the advantages of both top‐down patterning and bottom‐up synthesis, a new materials platform of patterned vertically grown gold nanowires (AuNWs) for constructing intrinsically stretchable electrodes, with high conductivity of 1288 S cm −1 at 0% and 152 S cm −1 at 170% strain, is introduced. Such patterned vertical AuNWs can be embedded in an elastomer matrix, leading to stretchable electrodes that are mechanically robust and durable. The interface between AuNWs electrodes and poly(3‐hexylthiophene) thin film shows ohmic contact for the entire strain regime from 0% to 100%, indicating low contact resistance. A stretchable organic transistor with ion gel as the dielectric is demonstrated, which can survive up to 100% strain without much performance degradation. The results indicate that our methodology may be extended to other organic semiconducting materials, hence, offering a general electrode materials platform for devising high performance intrinsically stretchable organic transistors. Abstract : Vertically grown gold nanowires can be patterned and successfully transferred to elastomer, offering a new materials platform for developing intrinsically stretchable electrodes. Such patterned electrodes have a high initial conductivity of 1288 S cm −1, stretchability of up to 170%, and possess low contact resistance with poly(3‐hexylthiophene). These attributes indicate potential applications in next‐generation intrinsically stretchable organic transistors.